2011
DOI: 10.1002/anie.201008013
|View full text |Cite
|
Sign up to set email alerts
|

Nanosizing Intermetallic Compounds Onto Carbon Nanotubes: Active and Selective Hydrogenation Catalysts

Abstract: Nanosized, yet ordered: Active and selective Pd2Ga intermetallic compounds supported on carbon nanotubes have been synthesized and applied to alkyne hydrogenation. Intermetallic compounds on the nanoscale are necessary to achieve high mass activity, whereas ordered structures within intermetallic compounds form high barriers for subsurface chemistry and prevent large active ensembles on Pd surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 36 publications
6
85
0
3
Order By: Relevance
“…7−9 Developing catalysts using intermetallic compounds could also benefit from their structural stability arising from highly favorable formation enthalpies. It has been shown that intermetallic compounds could maintain their surface structure under reaction conditions, 10 whereas the surface composition and structure of alloys usually change under different reaction environments. 11 Combined, these two features, unique electronic structure and high stability, potentially circumvent problems with traditional, supported multimetal/alloy catalysts, such as chemical heterogeneity of particles (which is detrimental to selectivity), broad distributions of active sites, surface segregation, and the formation of carbides or hydrides.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…7−9 Developing catalysts using intermetallic compounds could also benefit from their structural stability arising from highly favorable formation enthalpies. It has been shown that intermetallic compounds could maintain their surface structure under reaction conditions, 10 whereas the surface composition and structure of alloys usually change under different reaction environments. 11 Combined, these two features, unique electronic structure and high stability, potentially circumvent problems with traditional, supported multimetal/alloy catalysts, such as chemical heterogeneity of particles (which is detrimental to selectivity), broad distributions of active sites, surface segregation, and the formation of carbides or hydrides.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Active and selective Pd 2 Ga intermetallic compounds supported on CNT were used in alkynes hydrogenation. Ordered structures form high barriers for subsurface chemistry and prevent large ensembles on the Pd surface 19 . Also, surface inspection of intermetallic PdGa 1 1 1 ( ) reveals a smooth surface with an (1 × 1) unit cell where no segregation occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 35 is a typical example how the structure and composition of a bimetallic system are accessed by a combination of STEM with EDS, element mapping ( Figure 35a), and line scan (Figure 35b). 273 For the studied Pd−Ga catalyst used for alkyne-selective hydrogenation, STEM-EDX analysis and elemental maps reveal a homogeneous composition of Pd and Ga of an atomic ration of 2:1; that is, the bimetallic particle is Pd 2 Ga (Figure 35a). A TEM-EDX line scan shows that the composition of Pd 2 Ga particles remains unchanged after reaction (Figure 35b).…”
Section: Structure and Dynamics Of Bimetallic Particlesmentioning
confidence: 99%